Wearable Health Monitoring Terminal Supporting Edge Cloud Computing Collaboration - Liu, Mengzhuo; Gao, Xinyu; Wang, Shiyi; Du, Ziwei; Xing, Rong; Yang, Xiuyuan; Zheng, Yangyang (International Journal of Computer Science and Information Technology, 2024)
In view of the problems of data accuracy and reliability, health data processing and interpretation that exist in current wearable health monitoring devices, this paper designs a wearable measurement device based on the STM32F103VCT6 that can collect a variety of physiological signals in real time, such as electrocardiography, blood oxygenation and so on. Based on the consideration of data accuracy and reliability, the STM32F103VCT6 processor with high performance, low power consumption and high reliability is used as the main control chip, and at the same time, suitable FIR filter parameters are designed to filter out the electromyographic signals and the industrial frequency interference noise, so as to effectively remove the noise and the redundant frequency components, and make the waveforms more clear and intuitive, and the data more accurate and reliable. For the processing and interpretation of health data, the signal spectrum is analysed by FFT transform, and the data is sent to the cloud system through wireless WiFi module, and the cloud platform checks, parses, plots and stores the data in real time, which has been proved the effectiveness of the design scheme by testing it in the real environment and making samples.